Determinan Variasi Klaim Penyakit Stroke Peserta Jaminan Kesehatan Nasional Rumah Sakit X Sumatera Utara - Mahulae, Joan Xaveria; Ilyas, Jaslis (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Refers to IHME study in 2010 about Global Burden of Disease shows that stroke is one of the highest cause of mortality in Indonesia. While the expenditure by BPJS Health for stroke is the 2nd highest after heart disease. This study aims to determine the most dominant characteristics associated with the total claims of stroke patients covered by JKN for inpatient service at X Hospital by doing multivariate analysis with variable linear regression method. The most significant characteristics are type of health care, type of membership, length of stay age, and level of severity. The finding shows that X Hospital is still not optimal in providing services for stroke. Some feasible efforts that can be considered are increasing the neurovascular experts and providing better diagnostic equipments in order to deliver the necessary treatment.